2015
DOI: 10.1016/j.ecolmodel.2014.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Temporal fluctuations in the environment and intra-specific polymorphism: A model simulating the flowering phenology of gorse (Ulex europaeus)

Abstract: International audienceThe onset and conservation of genetic polymorphism is a major question in evolutionary ecology. The influence of temporal fluctuations in the environment was invoked by early theorists such as J.B.S. Haldane and S. Jayakar in a controversial article published in, 1963, but their frequently cited model has almost never been used with empirical evidence. In this paper,we present a simulation model inspired by the biology of common gorse (Ulex europaeus), a species which shows polymorphism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Guo et al (2015) studied uncertainty in ensemble modelling of species distribution models in predicting fish species distribution in aquatic ecosystems under the impacts of global climate change, and reported species distributed with a smaller range size of variables such as altitude and precipitation could be more accurately predicted than species with large range size. Rio et al (2015) developed a simulation model inspired by the biology of common gorse, a species which shows polymorphism of flowering phenology. The results showed that the combination of the two selective pressures acting on gorse flowering phenology can lead to fitness values meeting the Haldane and Jayakar's conditions on geometric and arithmetic means, and to long term maintenance of polymorphism.…”
mentioning
confidence: 99%
“…Guo et al (2015) studied uncertainty in ensemble modelling of species distribution models in predicting fish species distribution in aquatic ecosystems under the impacts of global climate change, and reported species distributed with a smaller range size of variables such as altitude and precipitation could be more accurately predicted than species with large range size. Rio et al (2015) developed a simulation model inspired by the biology of common gorse, a species which shows polymorphism of flowering phenology. The results showed that the combination of the two selective pressures acting on gorse flowering phenology can lead to fitness values meeting the Haldane and Jayakar's conditions on geometric and arithmetic means, and to long term maintenance of polymorphism.…”
mentioning
confidence: 99%